Setting the stage for the review of the international estimate of short-term intake (IESTI) equation. Issue 6 (3rd June 2018) - Richter, Anke; Sieke, Christian; Reich, Hermine; Ossendorp, Bernadette C.; Breysse, Nicolas; Lutze, Jason; Mahieu, Karin; Margerison, Sam; Rietveld, Anton; Sarda, Xavier; Vial, Gaelle; van der Velde-Koerts, Trijntje
ABSTRACT: In the framework of setting Maximum Residue Limits (MRLs) for pesticides, both chronic and acute health risks to consumers arising from the long-term and short-term dietary exposure to pesticide residues have to be assessed. The current internationally harmonized approach for assessing the acute dietary exposure is based on deterministic methods for calculating the IESTI (International Estimate of Short-Term Intake). Recently, it became apparent that the IESTI approach needs a revision in the light of new scientific and political aspects. The main reasons that require this review were the lack of an international harmonization of the methodology which implies trade barriers as well as difficulties in risk communication concerning the public trust in regulatory systems. The most recent milestone in the scientific debate on a possible revision of the IESTI equation was an international scientific workshop held in Geneva in September 2015. The main objectives of this meeting were the re-evaluation, and where possible, the international harmonization of the input parameters for the IESTI equations as well as the equations themselves. The main recommendations from the workshop were (i) to replace the highest residue and supervised trials median residue with the maximum residue limit (MRL), (ii) to use a standard variability factor of three, (iii) to derive the P97.5 large portion value from the distribution of consumption values of dietary surveys expressed as kg food/kg bw/d, and (iv) to remove the commodity unit weight from the equations. In addition, the application of conversion factors and processing factors was addressed. On the initiative of the (World Health Organization) WHO Collaborating Centre on Chemical Food Safety at the National Institute for Public Health and the Environment (RIVM), the Netherlands, an international working group with members from the French Agency for Food, Environmental and Occupational Health and Safety, France (ANSES), Australian Pesticides and Veterinary Medicines Authority, Australia (APVMA), German Federal Institute for Risk Assessment, Germany (BfR), Chemical Regulation Division, the United Kingdom (CRD), European Food Safety Authority (EFSA), and RIVM, the Netherlands was formed after the IESTI workshop to conduct a comprehensive impact assessment of the proposed changes of the IESTI equations.